2022
DOI: 10.3390/molecules27154926
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Natural Compounds in Paclitaxel-Induced Chronic Inflammatory Pain

Abstract: The current study explored the effects of natural compounds, berbamine, bergapten, and carveol on paclitaxel-associated neuroinflammatory pain. Berbamine, an alkaloid obtained from BerberisamurensisRuprhas been previously researched for anticancer and anti-inflammatory potential. Bergapten is 5-methoxsalenpsoralen previously investigated in cancer, vitiligo, and psoriasis. Carveol obtained from caraway is a component of essential oil. The neuropathic pain model was induced by administering 2 mg/kg of paclitaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Nerve ligation in CCI-model causes generation of free radicals which further damage nerve tissues resulting in progression and worsening of disease along with hyperalgesia and other pain-associated consequences [ 18 , 33 ]. Emodin treatment attenuated the enhanced LPO and NO levels and upregulated the diminished GST, GSH and CAT levels which is also in line with previous studies [ 19 , 34 ]. Hence, we can deduce that antioxidant effect of emodin also played a vital role in ameliorating pain and its related abnormalities by preventing oxidative damage to the nerve.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nerve ligation in CCI-model causes generation of free radicals which further damage nerve tissues resulting in progression and worsening of disease along with hyperalgesia and other pain-associated consequences [ 18 , 33 ]. Emodin treatment attenuated the enhanced LPO and NO levels and upregulated the diminished GST, GSH and CAT levels which is also in line with previous studies [ 19 , 34 ]. Hence, we can deduce that antioxidant effect of emodin also played a vital role in ameliorating pain and its related abnormalities by preventing oxidative damage to the nerve.…”
Section: Discussionsupporting
confidence: 92%
“…Post acclimatization, animals were placed in an enclosed chamber having mesh flooring and Von Frey filaments of 1, 2, 4, 6, 8, 10, 15 and 20 g were gradually applied at low pressure, in such a way that the filament bent for 2–3 seconds, onto the planter surface of the animal’s feet. A quick retreat or paw-licking was noted to detect mechanical allodynia [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently studies mainly focus on evaluating the effective index of medicine in the treatment of chronic pain through GST levels. For example, the natural compounds in Paclitaxel increased the protective GST levels in the sciatic nerve and spinal cord, 47 as well as the therapeutic effects of Atorvastatin 15 and Streptozotocin. 48 The fact that our findings also suggested that GST was associated with an increased incidence of dentoalveolar pain, while additional epidemiological research and more focused laboratory investigations are required to understand the biochemical and chemical biological underpinnings for these correlations.…”
Section: Discussionmentioning
confidence: 99%
“…The caraway plant yields carveol (CAR), an essential oil ingredient cultivated globally. Caraway includes pinene, thujene, phellandrene, camphene, limonene, and carvone ( Faheem et al, 2022b ). The selection of these compounds is based on their anti-inflammatory potential.…”
Section: Introductionmentioning
confidence: 99%